mprovement on the developed system for automation of cutting tools selection - Todić, Velimir (Journal of Production Engineering, 1994)
Tools which are used in manufacturing processes as cutting units in block-tool systems, either in conventional machining and technological systems or in the modern flexible manufacturing systems, have a significant influence on the aggregate quality of the machining process for a concrete part. Hereby tool changing systems and cutting abilities represent the most significant elements in tool quality especially in the utilization of flexible manufacturing systems and other NC-controlled technological systems. Efficient and high quality selection of cutting wilts le tools, requires development of the adequate systems for their automated selection. Such systems provide a basic prerequisite to a sophisticated and agile operation in the process planning in contemporary settings. The paper reviews improvements in the developed system for automated selection of cutting modules le tools, which pertains to the development of graphics support as well as the module for automated selection of optimized tools for single cuts within machining operations.